A qualificação de professores do ensino fundamental na escola estadual Girassol de Araguaína – TO. - Gomes, Dayane Rodrigues Simon (Universidade Federal do Tocantins, 2022)
This research approaches questions that comprehend the qualification professional process of teachers in the basic education. Our problem in this research is to know if the elementary teachers of Estadual Girassol School of Araguaína-TO, it has realized the profissional qualification during their path as faculty. For this purpose, we stabelished ours goals, that it has as main intention, to analyse how occur the qualification profissional process of teacher in the Basic Education at Estadual Girassol school of Araguaína-To; to identify the main problems that envolves the faculty qualification at school; to identify, how the teachers of Basic Education at Estadual Girassol School realized the profissional qualification, to their faculty activities.Therefore,inicially, we made the bibliographic revision, about the object of study and subsequently we performed the field research, we performed the field research, of qualitative stamp which the purpose it was to get results deeper and satisfactory a concerning the reality about the qualification of teachers process at school, the place of our research. The achieved results from analyses of the data revealed that although many advanced occured with relation the inicial formation of teachers, they do not come seeking to give continuity to the other levels of profissional qualification, due to many factors, between them the public politics´s lack more consistent and worried with teaching and with the qualities of work developed by teachers in classroom and consequently with their qualifications and the lack of involvement of school teachers in this process. Shortly, we understand that this work have importante contribuition to the new studies and research that study teachers´formation at public school education of Araguaína-To city and the others publics schools of our country